1993
DOI: 10.1021/bi00088a012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen exchange identifies native-state motional domains important in protein folding

Abstract: Effects of mutations on hydrogen exchange kinetics, structure, and stability suggest that the slow exchange core is a key element in protein folding. Single amino acid variants of bovine pancreatic trypsin inhibitor (BPTI) have been made with glycine or alanine replacement of residues Tyr 35, Gly 37, Asn 43, and Asn 44. The crystal structures of Y35G and N43G are reported [Housset, D., Kim, K.-S., Fuchs, J., & Woodward, C. (1991) J. Mol. Biol. 220, 757-770; Danishefsky, A. T., Housset, D., Kim, K.-S., Tao, F.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
175
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(183 citation statements)
references
References 75 publications
7
175
1
Order By: Relevance
“…Spectra were collected every 20 min for 16 h. The results showed that that all but six protons were exchanged within 20 min, the time required to acquire the first spectrum. The peaks that did persist were fully exchanged after 3 h. The exchange rate for the measurable peaks is consistent with the AG measured by urea denaturation (Kim et al, 1993). These results show that the majority of backbone NH groups of p16 are in very rapid exchange, therefore suggesting that p16 is a highly dynamic protein.…”
Section: Ja Boice and R Faimansupporting
confidence: 83%
See 1 more Smart Citation
“…Spectra were collected every 20 min for 16 h. The results showed that that all but six protons were exchanged within 20 min, the time required to acquire the first spectrum. The peaks that did persist were fully exchanged after 3 h. The exchange rate for the measurable peaks is consistent with the AG measured by urea denaturation (Kim et al, 1993). These results show that the majority of backbone NH groups of p16 are in very rapid exchange, therefore suggesting that p16 is a highly dynamic protein.…”
Section: Ja Boice and R Faimansupporting
confidence: 83%
“…We also measured protein dynamics using hydrogen-deuterium exchange rates as monitored by NMR. The rate at which amide protons exchange with solvent deuterons is an indication of the dynamics of a protein as well as the number of residues that are involved in the folding core (Kim et al, 1993). A sample of S-tagp16 was reconstituted in deuterated H,O and the NMR spectrum was compared to the NMR spectrum established for an identical sample reconstituted in H,O.…”
Section: Ja Boice and R Faimanmentioning
confidence: 99%
“…4b and formalized in reaction Scheme 1 (the infrared foldon was found later). This interesting possibility, that progressively slower exchanging sets of amide hydrogens might represent a sequential unfolding pathway, had been suggested much earlier on other grounds (Englander & Kallenbach, 1983;Kim et al 1993). …”
Section: Pufs To Pathwaysmentioning
confidence: 82%
“…It is particularly striking that at 5 "C, the N-terminal 310-helix and residues 54-56 of the C-terminal a-helix are more protected from exchange in Clarke et al, 1993;Kim et al, 1993;Woodward, 1993).…”
Section: Comparison Of Amide Proton Exchange Propertiesmentioning
confidence: 99%